Market constellations and macroeconomic policy-making: institutional impacts on economic performance - Arne Heise (Universität Hamburg, Department Wirtschaft und Politik, 2005)
Post Keynesian theory as opposed to Walrasian theory does not provide the foundations for a unique general equilibrium but claims the existence of multiple equilibrium positions. In this article, such a multiple of equilibrium positions is explained by different market constellations which are characterised by different sets of institutions. political and cultural factors and historical circumstance in general and can be formed by collective bargaining systems and Central Banking designs as well as implicit or explicit mechanisms of coordination between key macroeconomic policy areas in particular. A market participation theory of economic policy based on market constellations may help to bridge the gap between nomocratic policy denial and teleocratic policy euphoria.
Keywords: E12; E61; 300; Market constellations; Central Bank Independence; Collective Bargaining system; Wirtschaftspolitik; Markt; Geldpolitik; Finanzpolitik; Lohnpolitik; Inflation; Arbeitslosigkeit; Postkeynesianismus; Theorie; EU-Staaten